Pengembangan Usaha Kopi Cup Celup pada Kelompok Wanita Tani Kaba Indah Lestari di Desa Bandung Jaya Kabupaten Kepahiang Provinsi Bengkulu - Sri Wulandari; Fitri Yuwita; Murlena (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
This community service activity aims to enhance the capacity of the Kaba Indah Lestari Women Farmers Group (KWT) in developing cup-dip coffee products as an innovative business diversification effort that offers added value and market orientation. The main problems faced by the group include limited product innovation, the absence of standardized production procedures, and the lack of packaging design and visual appeal. The methods implemented in this program included delivering instructional materials, conducting Focus Group Discussions (FGD), demonstrations, and hands-on production training. The materials provided covered raw material standards, roasting technology, grinding, weighing, and packaging of cup-dip coffee. The FGD was conducted to design attractive packaging that aligns with the group’s identity. The results showed an increase in participants’ knowledge and skills in understanding production technology, as well as their ability to create new packaging designs ready to be used for product branding. Participants demonstrated strong enthusiasm and expressed commitment to continuing the production and marketing of the cup-dip coffee products. Overall, this community service activity had a positive impact on strengthening business capacity, increasing the added value of local coffee products, and supporting the economic independence of the KWT in Bandung Jaya Village.